Effectiveness of relational & personal savoring on mothers of children with autism spectrum disorder - Ng, Valerie Shi Hui (2018)
With the prevalence of Autism Spectrum Disorders (ASD) rising in Singapore, it is imperative to source for effective techniques to alleviate the significantly higher amount of parental stress, depression and anxiety that parents of children with ASD experience compared to parents of children with typical development. Savoring refers to the experience of focusing on a specific positive past event and this technique has been demonstrated to be beneficial for positive affect, depression and neuroticism. The aim of this study was to examine if savoring (personal & relational) would enhance parental satisfaction and positive affect in mothers of children with ASD. 20 participants completed an online questionnaire investigating the effectiveness of savoring on parental satisfaction and positive affect. The influences of parental stress, depression and anxiety were also examined. Mothers who engaged in personal savoring were significantly more likely to report enhanced positive affect as compared to mothers who engaged in relational savoring. Additionally, after savoring, mothers who reported higher levels of parental stress, depression and anxiety were significantly more likely to report enhanced parental satisfaction and positive affect as compared to mothers who reported lower levels of parental stress, depression and anxiety. Parental stress was also positively associated with self-reported levels of depression and anxiety. Results demonstrated that mothers' level of parental stress, depression and anxiety had differential impact on the effectiveness of savoring. As this area of research is relatively new, there is still much to be explored regarding the benefits of engaging in savoring for parents of children with ASD.